Traffic characteristics and interactions at signalised junctions - Lum, Kit Meng. (2008)
A data logger was conceptialised and modified for the research study. Loop sensors attuned with this logger were established to gather traffic and the crossing/stopping movements of vehicles during signal change interval. Two types of experiment designs were used.